Analisis Tata Letak Fasilitas Produksi Kerupuk untuk Meningkatkan Produktivitas (Studi Kasus: UD.MAWAR) - Ramadhan, Arif Rianta; Mundari, Siti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
UD. Mawar is a small-scale cracker manufacturing enterprise located in Menganti, Gresik, which requires efficient material flow to support its daily production activities. However, the existing facility layout presents inefficiencies such as long travel distances, backtracking, and suboptimal space utilization, resulting in increased transfer time, high material handling costs, and reduced productivity. This study aims to redesign the production layout using Activity Relationship Chart (ARC), Activity Relationship Diagram (ARD), supported by simulation modeling with FlexSim 2019. Findings show that the proposed U-Flow layout reduces monthly material travel distance from 11,616 m to 4,800 m (58.7%), decreases transfer time from 100.17 to 88.33 minutes (11.8%), and lowers handling costs from IDR 363,000 to IDR 150,000 (58.7%). Productivity increases from 239.5 to 271.7 kg/hour (13.4%). The redesigned layout is recommended to enhance operational efficiency.